KAJIAN EFEKTIVITAS PEMBAGIAN ZONASI SATUAN KAWASAN PENGEMBANGAN (SKP) WILAYAH PESISIR KABUPATEN PEKALONGAN - Eva Retnosari, Noptri Jumario (Prokons: Jurnal Teknik Sipil, 2018)
Coastal region of  Pekalongan Regency has many potential resources to develop such as marine fishery, fishery cultivation, tourism and fishery port. These potential resources influencing the coastal region because of the interaction between stakeholders. This intensif interaction potentially  effecting conflict of interest that threat the coastal ecosystem. Therefore, to ensure the sustainability development in coastal area, the government of Pekalongan Regency adopt Integrated Coastal Zone Management by means of zonation regulationThe objective of the research was to study the level of effectiveness of The Zonation of Pekalongan Coastal Area and determine alternative priority of coastal region development. The methodology research was a survey and to achieve these objective, two methods of analysis was used. Scoring methods conducted to determine the level of effectiveness of The Zonation of Pekalongan Coastal Area and an AHP Method used to determine alternative priority of coastal region development.Five indicator in this research to determine the level of effectiveness are physical condition of the area, economics aspect, space use accuracy, ICZM and regulation goal achievement. In order to determine alternative priority of coastal region development, the research results shows, that are three main priority components of coastal region development ; transportation system (0,2616), infrastructure development (0,2307) and improving the environment (0,1816). From Analytical Hierarchy Process, informan tent to prioriate SKP I (0,6205) as the main priority to develop coastal area. Henceforth are SKP II (0,2893) dan SKP III (0,0901) Keywords: effectiveness, zonation, integrated coastal zone management, coastal region development